Species diversity and habitat preferences of amphibian fauna in six protected areas of Bangladesh (Bangladesh Journal of Zoology, 2015)
Study on amphibian species diversity and habitat preferences was conducted in six protected areas of Bangladesh between March 2011 and July 2012. A total of 32 species of amphibians were recorded under six families. Family Dicroglossidae comprised the highest number of species (12) where Bufonidae the lowest (1 species). Among these species 34% were uncommon, 31% common, 19% rare and 16% very common. Alpha diversity was the highest in Dudpukuria- Dhopachari Wildlife Sanctuary (28) and the lowest in Sitakunda Eco-park (13). Beta diversity was the highest (11) between Inani Protected Forest and Sitakunda Eco-park and the lowest (3) between Dudpukuria-Dhopachari Wildlife Sanctuary and Teknaf Wildlife Sanctuary. Jaccard index of similarity among the amphibian communities was the highest (J=0.90) between Dudpukuria-Dhopachari Wildlife Sanctuary and Teknaf Wildlife Sanctuary and the lowest (J=0.54) between Inani Protected Forest and Sitakunda Eco-park. Fifty percent of the species were found to use more than two habitats, while only 16% species were restricted to a single habitat. Significant number of the species (20 species) were found to use forest edges, aquatic environment (19 species), forest floor (15 species), agricultural land (13 species), bushes (7 species) and tree habitats (3 species).Bangladesh J. Zool. 42(1): 105-116, 2014